The Effect of Ovaprim Hormone Injections with Different Doses on Spawning Performance of Bader Abang Fish (Barbonymus balleroides) - Adi, Rinaldo Axlvianto (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2025)
Bader abang fish (Barbonymus balleroides) belongs to the Cyprinidae family which is a freshwater fish species native to Indonesia. The bader abang fish hatchery process to date uses a semi-artificial technique with ovaprim hormone injection. This study aims to determine the effect of different ovaprim hormone injections on bader abang fish spawning performance. This research was conducted at the Fish and Environmental Health Laboratory in Pasuruan, East Java from June to August 2024. Ovaprim hormone injection was done in the intramuscular part of the fish using 2 treatments, namely P1: dose of 0.1 ml / kg broodstock, P2: dose of 0.2 ml / kg broodstock. The parameters observed in this study were fecundity, degree of fertilization, and hatchability. Ovaprim hormone injection of 0.2 ml/kg brood weight of bader abang fish obtained higher parameter values compared to ovaprim hormone injection of 0.1 ml/kg brood weight. The results showed that the fecundity of P1 was 14,516 eggs and P2 was 16,250 eggs, Fertilization rate P1 was 89.5% and P2 was 91.8%, Hatching rate P1 was 86.2% and P2 was 90.9%.